Ibadah bagi Pembentukan Spiritualitas - Nainggolan, Alon Mandimpu; Keryapi, Donald Steven; Langga, Mersi (SEKOLAH TINGGI TEOLOGI KIBAID MAKALE, 2025)
Abstract Spiritual formation for theology study program students is very important, in addition to academic and practical formation. Deep attention to worship as a basis for spiritual formation will lead theology study program students to be ready to become church ministers. The fact in the field is that worship has not been maximally utilized by undergraduate students of the Jakarta School of Theological Philosophy or Jakarta Theological Seminary. This study aims to analyze, describe, and construct how worship as a basis for forming spirituality for undergraduate students of STFT Jakarta in living out their identity as prospective church servants. This research uses a qualitative research method that is descriptive analysis, with three data collection techniques namely document study, observation, and interviews. The results of this study confirm that worship is the basis for the formation of essential spirituality for STFT Jakarta undergraduate students in living their identity as prospective church servants or community servants. There are effectiveness, significance, impact, and values of worship as the formation of spirituality.